A high-responsivity CsPbBr3 nanowire photodetector induced by CdS@CdxZn1−xS gradient-alloyed quantum dots. Issue 6 (18th May 2022) - Wei, Ying; Liu, Xiao; Miao, Yu; Liu, Yuxin; Wang, Chuanglei; Ying, Xiangjing; Zhang, Gaotian; Gu, Huaimin; Zhang, Menglong; Chen, Hongyu
Abstract : We have developed a novel QD/CsPbBr3 nanowire (NW) hybrid structure photodetector. The responsivity of the CsPbBr3 NW photodetector has been significantly improved via integrating gradient-alloyed QDs with CsPbBr3 NW as a photoactive layer. Abstract : Benefitting from excellent thermal and moisture stability, inorganic halide perovskite materials have established themselves quickly as promising candidates for fabricating photoelectric devices. However, due to their high trap state density and rapid carrier recombination rate, the photoelectric conversion efficiencies of current inorganic halide perovskite materials are still lower than expected. Here, after systematic research on the optoelectronic properties of CsPbBr3 nanowires (NWs) decorated with binary CdS quantum dots (QDs), CdS@ZnS core/shell QDs, and gradient-alloyed CdS@Cd x Zn1− x S QDs, respectively, we proposed a facile method to improve the quantum efficiency of perovskite-based photodetectors with low cost, in which the aforementioned QDs are firstly integrated with CsPbBr3 NWs, which act as a photosensitive layer. Notably, the responsivity of the CsPbBr3 NW photodetector decorated with CdS@Cd x Zn1− x S QDs was enhanced about 10-fold compared to that of pristine CsPbBr3 NW devices. This value is far superior to those for hybrids composed of binary CdS QDs and CdS@ZnS core/shell QDs. The high responsivity enhancement phenomena are interpreted based on the unique funnel-shaped energy level of CdS@Cd x Zn1− x S QDs, which is favorable for light-harvesting and photocarrier separation. This work indicates that our unique QD/NW hybrid nanostructure is a desirable building block for fabricating high-performance photodetectors.